Calorific value analysis of coastal plastic waste for electric power generation in Selayar Islands - Abeng, Dwi Novalita Tanri; Wahab , Abdul Wahid; Monoarfa, Winarni; Demmalino, Eymal Bahsar (Edelweiss Applied Science and Technology, 2025)
The electricity reserve in the South and Southeast Sulawesi (SULBAGSEL) region in March 2024 was only 167.01 MW, indicating a potential energy crisis. Selayar Islands Regency, with an electrification ratio of just 57%, is among the lowest in South Sulawesi. With a population of 140,312 and household waste production of 25,774 tons per year, the region also faces serious waste management challenges. Notably, coastal plastic waste contributes around 2.179 tons per day. This study aims to analyze the potential for generating electrical energy from coastal plastic waste based on its calorific value. The analysis was conducted using proximate analysis, followed by energy potential estimation using both traditional and Bento methods. The results show that polystyrene (PS) has the highest energy potential at 733,297 kWh/year, while low-density polyethylene (LDPE) has the lowest at 514,140 kWh/year. The findings confirm that higher net calorific value (NCV) corresponds to greater electricity generation potential. The novelty of this study lies in integrating coastal plastic waste profiling with energy conversion analysis specific to a remote island context. As a recommendation, further research should explore the development of small-scale waste-to-energy facilities tailored to isolated coastal areas such as the Selayar Islands.